ENGLISH LANGUAGE BARRIERS IN TOURISM COMMUNICATION AT SOMI BEACH - Zamasi, Daniel Setiawan; Harefa, Afore Tahir; Hia, Maria Putri Cantika; Waruwu, Fitri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Tourism communication constitutes a strategic element in shaping service quality, tourist experiences, and destination sustainability, particularly in emerging tourism areas. Somi Beach in Nias, Indonesia, possesses significant natural and cultural potential; however, its development continues to be constrained by limitations in English communication skills among local tourism actors. This study aims to examine the forms, causes, and impacts of English language barriers in tourism communication, as well as to identify the adaptive strategies employed by local tourism actors in their interactions with international visitors. The study adopts a descriptive qualitative approach, with data collected through in-depth interviews with local tour guides, homestay owners, food vendors, and tourism managers, complemented by direct field observations of service interactions. The findings indicate that English language barriers primarily occur at the level of functional communication, including difficulties in explaining tourist attractions, providing service information, responding to visitor inquiries, and engaging in intercultural interaction. These barriers are influenced by limited formal English education, insufficient tourism-specific English training, low frequency of English use, and a lack of confidence in oral communication. The impacts are reflected in reduced service effectiveness, the occurrence of misunderstandings, decreased tourist satisfaction, and missed opportunities for destination promotion. Despite these challenges, local tourism actors employ adaptive communication strategies, such as the use of basic English expressions, non-verbal communication, translation applications, and peer assistance. This study underscores the importance of developing context-based English language capacity as part of human resource strengthening to support sustainable tourism growth in emerging coastal destinations. ABSTRAK Komunikasi pariwisata merupakan elemen strategis dalam membangun kualitas layanan, pengalaman wisatawan, dan keberlanjutan destinasi, khususnya pada kawasan wisata yang sedang berkembang. Pantai Somi di Nias, Indonesia, memiliki potensi alam dan budaya yang besar, namun pengembangannya masih menghadapi kendala pada aspek komunikasi bahasa Inggris di kalangan pelaku pariwisata lokal. Penelitian ini bertujuan untuk mengkaji bentuk, penyebab, dan dampak hambatan bahasa Inggris dalam komunikasi pariwisata, serta mengidentifikasi strategi adaptif yang digunakan oleh pelaku pariwisata lokal dalam berinteraksi dengan wisatawan internasional. Penelitian menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui wawancara mendalam terhadap pemandu wisata, pemilik homestay, penjual makanan, dan pengelola pariwisata, serta observasi langsung terhadap interaksi layanan di lapangan. Hasil penelitian menunjukkan bahwa hambatan bahasa Inggris terutama muncul pada komunikasi fungsional, seperti menjelaskan daya tarik wisata, menyampaikan informasi layanan, menanggapi pertanyaan pengunjung, dan melakukan interaksi lintas budaya. Hambatan tersebut dipengaruhi oleh keterbatasan pendidikan formal bahasa Inggris, minimnya pelatihan bahasa Inggris pariwisata, rendahnya intensitas penggunaan bahasa Inggris, serta kurangnya kepercayaan diri dalam komunikasi lisan. Dampaknya terlihat pada menurunnya efektivitas layanan, munculnya kesalahpahaman, berkurangnya kepuasan wisatawan, dan terbatasnya peluang promosi destinasi. Meskipun demikian, pelaku pariwisata lokal mengembangkan strategi komunikasi adaptif melalui penggunaan ungkapan dasar bahasa Inggris, bahasa nonverbal, aplikasi terjemahan, dan bantuan sesama. Studi ini menegaskan pentingnya pengembangan kapasitas bahasa Inggris berbasis konteks lokal sebagai bagian dari penguatan sumber daya manusia untuk mendukung pertumbuhan pariwisata berkelanjutan di destinasi pesisir yang sedang berkembang.